A note on geographical systems and maps of Montserrat - Odbert, Henry M.; Grebby, Stephen (Geological Society, 2014)
It is often critically important that geospatial data are measured and mapped accurately, particularly for quantitative analyses and numerical modelling applications. Defining a geographical coordinate system requires a non-unique combination of geodetic techniques (e.g. ellipsoids, projections and geoids). The choice of geographical system presents scope for ambiguity and confusion about geographical data, especially those archived without appropriate metadata. Experience has shown that these confusions have been a repeating source of either frustration or inadvertent error for those using geographical data from Montserrat. This is, in part, probably due to common usage of multiple datums and the existence of numerous topographical datasets recorded during the past 150 years. Here, we attempt to provide a brief introduction to geodetic principles and their application to Montserrat geographical data. The differences between common datums are illustrated and we describe variations in magnetic declination as they apply to field use of magnetic instruments. We include a record of the source of the large-scale mapping datasets that have been used and analysed ubiquitously in the literature. The descriptions here are intended as an introductory reference resource for those using geographical data from Montserrat.